Identifikasi dan Dominasi Parasit pada Sumber Daya Ikan Hias di Danau Lais Kalimantan Tengah - Rosita Rosita (Fakultas Peternakan Universitas Kristen Palangka Raya, 2012)
This study aims to identify and inventory of potentially pathogenic species of parasites cause disease in ornamental fish, both caught in the Lais lake and the domestication activities. Beside is to know the relationship between water quality with a prevalence, intensity and dominance of parasites that attack ornamental fish in domestication. The reseach activities were conducted since January 20, 2010 until March 16, 2010. The fish samples collected from the fishermen were identificated and inventoried by means of recording of parasite type, amount and organs attack the fish using the identification book (Kabata, 1985) and the identification key of parasite by Bykhovskaya, et al. (1964) and calculated the value of domination. The results showed four parasitic protozoan species were Myxobolus sp, Glossatella sp, Vorticella sp., Chilodonella sp. and one species of non-protozoan (worms) was Dactylogyrus sp. in Lais lakes and in the domestication.